2021
DOI: 10.3390/insects12040327
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacterial and Fungal Communities of the Wild and Laboratory-Reared Thitarodes Larvae, Host of the Chinese Medicinal Fungus Ophiocordyceps sinensis on Tibetan Plateau

Abstract: By employing a culture-dependent and -independent 16S rRNA and ITS gene high-throughput sequencing analyses, comprehensive information was obtained on the gut bacterial and fungal communities in the ghost moth larvae of three different geographic locations from high-altitude on Tibet plateau and from low-altitude laboratory. Twenty-six culturable bacterial species belonging to 21 genera and 14 fungal species belonging to 12 genera were identified from six populations by culture-dependent method. Carnobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The relative abundances of anaerobes were significantly different in insects, and the gut bacterial diversity was impacted by host environmental location, food, growth status, and phylogeny ( Yun et al, 2014 ). Liu et al (2021) reported that larval bacterial communities differed between laboratory and wild populations of ghost moths ( Thitarodes sp.). Yu et al (2021) compared the microbiota in Leptinotarsa decemlineata (Say), Colorado potato beetles, derived from distinct geographic locations in China, and found that order and genus were proper taxonomic categories to discriminate the geographical locations of Colorado potato beetles.…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundances of anaerobes were significantly different in insects, and the gut bacterial diversity was impacted by host environmental location, food, growth status, and phylogeny ( Yun et al, 2014 ). Liu et al (2021) reported that larval bacterial communities differed between laboratory and wild populations of ghost moths ( Thitarodes sp.). Yu et al (2021) compared the microbiota in Leptinotarsa decemlineata (Say), Colorado potato beetles, derived from distinct geographic locations in China, and found that order and genus were proper taxonomic categories to discriminate the geographical locations of Colorado potato beetles.…”
Section: Introductionmentioning
confidence: 99%
“…This process maintains a steady nutritional background of O. sinensis fruiting bodies regardless of how they are produced. In our parallel studies, we found that bacterial and fungal communities varied in wild and laboratory Thitarodes lines [48]. Therefore, it is likely that O. sinensis may employ innate metabolism pathways to digest the host/medium and produce the fruiting body.…”
Section: Situation Dependent Metabolomics Of O Sinensismentioning
confidence: 79%
“…A trunk diet might result in reproductive isolation between E. brandti and E. scrobiculatus , as the relative abundance of Wolbachia and gene flow toward the MK-infected island is increased when the relative abundance of Spiroplasma is high ( Engelstadter et al, 2008 ; Yoshida et al, 2019 ). However, some previous studies have shown that the abundance of Wolbachia in the gut is higher in laboratory environments, but the reason for this pattern remains unclear ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%